Students’ Learning Difficulties in Mathematics: How Do Teachers Diagnose and How Do Teachers Solve Them? - Rani Febriyanti; Ali Mustadi; Mohammad Adam Jerussalem (Jurnal Pendidikan Matematika, 2021)
This study aims to find out how teachers diagnose to determine students’ learning difficulties, especially in Mathematics in Elementary Schools. There are four aspects discussed in this study, including the teachers’ perception of students’ learning difficulties, teachers’ practice in connection with diagnosing students’ learning difficulties, teachers’ actions in response to the results of the diagnosis, parties involved regarding students’ learning difficulties. The research method used was descriptive qualitative with 13 teachers as the subject selected by purposive sampling. The data were obtained through interviews with classroom teachers, both from private and public schools, especially in North Borneo. The findings in this study show that the teachers use various ways to diagnose and overcome students’ learning difficulties. There are 3 ways that teachers do to diagnose learning difficulties in Mathematics, including tests, observations and interviews. While the ways to overcome them are to do remedial, provide tutoring individually, provide additional hours for students who have learning difficulties in Mathematics and involve students in learning. The method used has been effective, proofed by changes in students’ understanding and improvement in students’ learning outcomes. This study offers elementary school teachers ways that can be carried out to diagnose and overcome students’ learning difficulties in Mathematics.